The effect of microwave irradiation on the kinetics and activation thermodynamics of ring‐opening polymerization of ε‐caprolactone. Issue 17 (7th June 2013) - Yamada, Shinji; Takasu, Akinori; Kawamura, Kazuhiko
ABSTRACT We examined the ring‐opening polymerization of ε‐caprolactone in toluene between 50 and 70 °C, and catalyzed by some Lewis and Brønsted acids to investigate the effects of microwave versus conventional heating on the kinetics and activation thermodynamics of the reaction. The polymerizations proceeded more rapidly when microwave heating, instead of conventional heating, was used to control the temperature. The number‐average molecular weight (Mn) of the polymer could be controlled even when microwave heating was used. To identify which thermodynamic activation constants were responsible for the accelerated polymerizations, we performed the reaction at different temperatures to obtain data for the Arrhenius and Eyring equations. Although the values for the activation energies and the activation enthalpies were larger when microwave heating rather than conventional heating was used, the frequency factors and the activation entropies (ΔS‡) over compensated for the less favorable activation energies and enthalpies. The more favorable ΔG‡ found for the microwave‐assisted polymerizations mainly reflect the larger ΔS‡ values, and the rate accelerations appear to be a consequence of differently arranged intermediates and/or transition states. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3732–3739